Development of pest management modules and their economic evaluation for legume pod borer, Maruca vitrata (Pyralidae: Lepidoptera) incowpea (Vigna unguiculata) - KODANDARAM, M H; WANGI, NAGARATNA; SABALE, P R; B, MANU; B, REVANAPPA (The Indian Journal of Agricultural Sciences, 2026)
Legume pod borer, Maruca vitrata (Geyer) is a major constraint in production of cowpea [Vigna unguiculata (L.) Walp.] in India. A field experiment was conducted during rainy (kharif) season of 2021–22 and 2022–23 at ICAR-Indian Institute of Pulses Research, Regional Research Station, Dharwad, Karnataka to evaluate different pest management modules, viz. bio-intensive, integrated and chemical module including an untreated control against legume pod borer in cowpea. All the pest management modules were found to be significantly superior over control in terms of pest reduction. Based on pooled average data of two-year study, integrated module comprising sequential spray of chlorantraniliprole 18.5 sc @0.5 mL/L, followed by botanical insecticide, azadirachtin 0.15% @4 mL/L and biorational insecticide, emamectin benzoate 5 g @0.5 g/L at 50% flowering at 10 days interval, was found effective with lowest pod damage of 11.88% and gave 65.97% protection over untreated control. Highest grain yield (1191.73 kg/ha) with 83.19% increase over untreated control, high benefit:cost ratio (1:2.05) and incremental benefit:cost ratio (2.64) were obtained in integrated module. This module reduced the grain yield loss to the extent of 45.41% whereas, the bio-intensive module and chemical module reduced the loss of grain yield up to 28.25 and 27.45%, respectively from pod borer damage. Thus, integrated module developed may be adopted to reduce the damage by pod borer in cowpea.